Contractile activity of vascular smooth musclesin hypoxia; Journal of Hypertension; Vol. 33, e-Supplement 1 : ESH 2015 Abstract Book - Birulina Yu. G. Yuliya G.; Smagly L. V. Lyudmila Vyacheslavovna; Gusakova S. V. Svetlana Valerjevna; Kovalev I. V. Igor Viktorovich; Nosarev A. V. Aleksey Valerievich; Aleinik A. N. Aleksandr Nikonorovich (2015, 2015)
Title screen